Body, Nature, Language: Artisans to Artists in the Commodification of Authenticity - Heller, Monica; Pietikäinen, Sari; da Silva, Emanuel (Anthropologica, 2017)
This article examines processes of authenticating and selling handicrafts at the conjuncture of cultural pride and economic profit in two peripheral sites (Finnish Sámiland and rural Québec), under shared conditions of late capitalism and globalising political economies. These conditions (re)structure traditionalist and modernist discourses about artisans’ historical bodies, their connections to the local land (nature), and how they interactionally authenticate and sell their products through language. Under these conditions, the commodification of authenticity pushes artisans and handicrafts beyond being emblems of national belonging and collective tradition, and toward individualised, artistic commercial production with greater or lesser ties to post-national cosmopolitanism.